Akibat Hukum Perjanjian (Akad) dan Terminasi Akad - Meri Piryanti (AT-Tahdzib: Jurnal Studi Islam dan Muamalah, 2014)
Basically sphere of human life in this world rests on two kinds of relationship, that is vertical to Allah and Horizontal ( Muamalah ) , this article discusses the Tenets of the emphasis on the three systems of the Agreement: Customary law , Civil Law ( KUHP) and Islamic Law . By using a comparative approach of this paper is expected to lead to the conclusion that can be justified .